Pengaruh Model Contextual Teaching and Learning terhadap Kemampuan Literasi Sains Siswa Kelas V SDN Kraton 3 - Ainun Farodisa; Bagus Rahmad Wijaya (Universitas Maritim AMNI Semarang, 2023)
This study aims to determine whether or not there is an effect of using the Contextual Teaching and Learning (CTL) learning model on Science Literacy Ability in Theme 8 Sub-theme 2 Class V SD Negeri Kraton 3 Bangkalan Regency. This research is a quantitative study with a quasi-experimental design with nonequivalent control group design. The sampling technique in this research is a saturated sample consisting of all 57 students in class V. The instrument that is used first goes through a process of validity testing and reliability testing to find out whether it is feasible or not to be used. The prerequisite test used is the normality test and homogeneity test. The hypothesis test used in this study is the independent sample t test. All tests were calculated with the help of IBM SPSS 25. Based on the results of the analysis of the t-test data, the tcount > ttable (8.125 > 2.004) and the Sig. (2-tailed) < 0.05 (0.000 < 0.05) which means that Ho is rejected and Ha is accepted, which means that there is a difference between the experimental class and the control class. if there is a difference then there is an influence. So that it can be interpreted that there is an influence on the application of the Contextual Teaching and Learning (CTL) learning model on Science Literacy Ability in Theme 8 Sub-theme 2 Class V SD Negeri Kraton 3 Bangkalan Regency.